Interaction between nearby strangers: serendipity and playfulness - Paasovaara, Susanna; Lucero, Andrés; Porcheron, Martin; Paavilainen, Janne; Aliakseyeu, Dzmitry; Olsson, Thomas (2016)
“Nearby strangers” provides an interestingly paradoxical space for interaction design. There are various social norms, cultural practices, and privacy concerns hindering interaction with nearby strangers, but by ignoring them, people constantly miss social opportunities. Technology enabling ad-hoc interactions between co-located people has been explored for years in research but real-life applications are still rare. The potential focus areas include increasing awareness of social possibilities; light-weight playful interactions, play and gaming; serendipitous and ad hoc social interaction; anonymous exchange of content; matching interests for various purposes; icebreakers and provocation to interact, and ambient representation of the nearby strangers. This workshop convenes researchers and practitioners to gather and advance the state of research on interactions between nearby strangers. We aim to explore this design space and collaboratively identify new research and design opportunities that novel communication technology creates.